Does Predation Exacerbate the Risk of Endosymbiont Loss in Heat Stressed Hermatypic Corals? Molecular Cues Provide Insights Into Species-Specific Health Outcomes in a Multi-Stressor Ocean - Madeira, Carolina; Dias, Marta; Ferreira, Ana; Gouveia, Raúl; Cabral, Henrique; Diniz, Mário S.; Vinagre, Catarina (Frontiers in Physiology, 2022)
Ocean warming has been a major driver of coral reef bleaching and mass mortality. Coupled to other biotic pressures, corals’ ability for acclimatization and adaptation may become compromised. Here, we tested the combined effects of warming scenarios (26 °C, 30 °C and 32 °C) and predation (wound vs no wound) in coral health condition (paleness, bleaching and mortality), cellular stress responses (heat shock protein 70 kDa Hsp70, total ubiquitin Ub, and total antioxidant capacity TAC) and physiological state (integrated biomarker response index, IBR) of seven Scleractinian coral species, after being exposed for 60 days. Results show that although temperature was the main factor driving coral health condition, thermotolerant species (Galaxea fascicularis, Psammocora contigua and Turbinaria reniformis) displayed increased paleness, bleaching and mortality in predation treatments at high temperature, whereas thermosensitive species (Acropora tenuis, Echinopora lamellosa and Montipora capricornis brown and green morphotypes) all died at 32 °C, regardless of predation condition. At the molecular level, results show that there were significant main and interactive effects of species, temperature and predation in the biomarkers assessed. Temperature affected Hsp70, Ub and TAC, evidencing the role of protein folding and turnover, as well as reactive oxygen species scavenging in heat stress management. Predation increased Hsp70 and Ub, suggesting the activation of the pro-phenoloxidase system and cytokine activity, whereas the combination of both stressors mainly affected TAC during moderate stress and Ub under severe stress, suggesting that redox balance and defence of homeostasis are crucial in tissue repair at high temperature. IBR levels showed an increasing trend at 32 °C in predated coral fragments (although non-significant). We conclude that coral responses to the combination of high temperature and predation pressure display high inter-species variability, but these stressors may pose a higher risk of endosymbiont loss, depending on species physiology and stress intensity.